Hubungan Antara Karakteristik Wanita Penjaja Seks (WPS) dengan Tingkat Pengetahuan Tentang Infeksi Menular Seksual (IMS) - Lisus Setyowati; Malinda Capri N S; Ria Chandra Kartika; Faiqatul Hikmah; Dia Bitari Mei Yuana (Indonesian Health Issue, 2025)
Background: Phenomenon of Sexual Transmitted Disease (STIs) become higher in Indonesia. Female Sex Workers (FSW) have bigger risk to get STIs because of their jobs. Mostly, STIs are asymptomatic and when it becomes symptomatic then it needs long time to be exposed. Good understanding about STIs is important for FSW in an effort to prevent transmission of STIs to themselves and customers. Aim: The aim of the research was to determine the relationship between characteristics of FSW and the level of knowledge about STIs. Method: This research was quantitative analysis . The research sample consisted of all FSW in the localization, Jember Regency and was conducted during August 2024. The data source used was primary data obtained from interviews and filling out questionnaires. The data was analyzed by Spearman Rank test with the SPSS application . Result: There is a relationship between duration of service of FSWs and the level of knowledge about STIs (p-value 0.04<0.05). This research examines four FSW characteristics: length of service, marital status, age, and final educational attainment. Only duration of service has a correlation with STIs knowledge out of the four traits. Productive age range, peer relationship and easier access to social media is becoming strong reasons.